Peace as an Authentic Foundation of Education from the Confucian Perspective: A Nigerian Situation - Afen Pius Ohere (PREDESTINASI, 2021)
This paper concerns itself with a discussion on “Peace as an Authentic Foundation of Education from the Confucian and Perspectives: A Nigerian Situation.” Nigerian System of Education values little or no peace. So as a country she had been severally threatened by social vices such as kidnappings, political thuggery, gang robbery, ethnic clashes, militancy, and religious extremism. These social menace had grossly affected the educational activities in the country, thereby caused the students, the teachers/Lecturers and the general society to face suffering ranging from death to ignominy (great dishonor, shame, or humiliation), anxieties, infirmities, miseries and hunger. Man is encompassed with evils and oppressed with anguish of spirit. The human existence is dolorous, plaintive, sorrowful, mournful, melancholic, pathetic, pitiful, sympathetic, doloroso and ponderously sad. These stripped man of his seamless garment of peace and happiness thereby leaving man with bitter tears. However, Confucius’ Five Relationships will be used to attempt solution to the absent of peace in our academic system in Nigeria. Confucius said that Men have innate desire for peace. To be more realistic; for any meaningful development to happen in any society, such society must necessarily experience social stability. When there is cohesion and harmony in the society; achievement and progress become easy. Unless men live in peace, the proper dispositions that determine progress will be illusive, false and mentally misrepresented. Critical and Clarification are the methods used in this paper. The paper advocated the “give peace a chance” to be used as a working tool for educational advancement in Nigeria.